PENGEMBANGAN AKTIVITAS WISATA DI TAMAN HUTAN RAYA IR. H. DJUANDA BANDUNG JAWA BARAT - Arief, Andi Moh. Rifiyan (SOROT, 2013)
Djuanda forest park based RIPPDA Prov. Jabar in 2005 isone tourist attraction that supports the development of mountainousnature of urban and tourist areas Bandung education. At this time,tourism activities in the forest park can be said Djuanda less variedand not utilize the full potensial optimaly. This is evident from theclose of the management of some the activities alredy underway.Closing the management of this activity is not offset by the newtourist activities, which led to the visitors who come today are lesslikely to have the option of doing tourist activities. Related to theabove, in support of the position Djuanda forest park as a touristattraction mountainous landscape that supports the development ofurban and tourist areas Bandung education is deemed necessary tocarry out the development of tourism activities.